Individualisme Gen Z sebagai Tantangan Kolektivisme di Indonesia - Rahmatia, Ashari; Sukmana, Oman; Susilo, Rachmad Kristiono Dwi (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
This article aims to explore how Generation Z's individualism has implications for the collectivism of the Indonesian nation, the study was conducted using a qualitative descriptive method where data was obtained through the collection of library studies from various literature such as books, articles, journals, news portals, and official websites. This article shows that Generation Z's individualism is caused by the complexity of the current of modernization marked by technological advances and globalization, resulting in materialistic and consumerist attitudes towards young people, this makes it easy for foreign values ​​and cultures to be easily accessed and makes local cultures which are the identity of the nation such as mutual cooperation slowly forgotten by the younger generation.